SAT0486 Reference Intervals for Bone Turnover Markers in Spanish Premenopausal Women. (10th June 2014) - Guañabens, N.; Filella, X.; Monegal, A.; Gomez-Vaquero, C.; Bonet, M.; Buquet, D.; Casado, E.; Cerda, D.; Erra, A.; Martinez, S.; Montala, N.; Pitarch, C.; et al.
Abstract : Background: Bone turnover markers (BTMs) are used in clinical practice for assessing patients with osteoporosis and their treatment. In Spain it is necessary to fine-tune the reference intervals, since they were established years ago in a low number of individuals. Objectives: The aims of this study were to establish robust reference intervals for BTMs in healthy young premenopausal Spanish women and to investigate the factors influencing BTMs. Methods: 185 women aged 35 to 45 yrs. from 13 centres in Catalonia were recruited. Blood and second void urine samples were collected between 8 and 10 a.m. after an overnight fast. Serum PINP and βCTX were measured by two automated methods (Elecsys, Roche a and IDS-ISYS, Immunodiagnostic Systems b ), bone ALP by ELISA (IDS, Vitro), osteocalcin by IRMA (Cis Bio) and urinary NTX by ELISA (Osteomark, Vitro). PTH and 25OHD levels were measured in all participants, who completed a questionnaire on lifestyle factors. A quantile regression was fit to estimate the 5%, 50% and 95% percentiles for the BMTs, and the Fisher's exact test and non-parametric tests were used to assess the influence of factors on BTMs. Results: The median (P5-P95) for BTMs were: Bone ALP 9.3 (6.0-13.8) ng/ml, PINP a 35.9 (20.8-60.6) ng/ml, PINP b 35.8 (20.8-64.9) ng/ml, NTX 32.7 (19.3-68.9) nM/mM, CTX a 0.250 (0.137-0.480) ng/ml, CTX b 0.246 (0.107-0.541), Osteocalcin 14.0 (8.0-23.0) ng/ml. Oral contraceptive pills (OCPs) were reported in 10.9% of participants, mean BMI was 23 and 60% had 25OHD levels lower than 20 ng/ml. Women on OCPs had lower PINP levels (p=0.007).25OHD levels didn't influence BTMs, but low BMI was associated with higher levels of almost all BTMs. Conclusions: In conclusion, robust reference intervals for BTMs in a southern European country are provided. Acknowledgements: This study was funded by a research grant from de Societat Catalana de Reumatologia. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1755